Obstetric violence in a group of Italian women: socio-demographic predictors and effects on mental health. Issue 11 (1st November 2022) - Scandurra, Cristiano; Zapparella, Rosanna; Policastro, Marilina; Continisio, Grazia Isabella; Ammendola, Alessandra; Bochicchio, Vincenzo; Maldonato, Nelson Mauro; Locci, Mariavittoria
Abstract: This study had two aims: (1) to explore the types and incidence of obstetric violence (OV) in a group of Italian women, as well as associated socio-demographic factors; and (2) to assess whether OV affects women's mental health (e.g. psychological distress and post-traumatic stress). A web-based cross-sectional study was conducted with 282 Italian women. Women answered questions on socio-demographic factors, childbirth characteristics, OV and mental health. Multiple linear regression analyses assessing the predictive role of socio-demographic and childbirth characteristics on OV were conducted. Additionally, hierarchical multiple linear regression analyses assessing whether OV affected women's mental health were also carried out. More than three quarters of the sample (78.4%) had experienced at least one type of OV (55.5% of non-consented care and 66.4% of abuse and violence). The factors most associated with OV were younger age, low educational level, not having attended a prenatal childbirth preparedness course, and having given birth naturally. The form of OV that most affected women's mental health was that linked to abuse and violence rather than non-consented care. Study findings shed light into addressing OV from a multidimensional perspective.